Comparison of the Effects of Two Different Low-Doses of Isobaric Bupivacaine on Intraoperative Hemodynamics under Spinal Anaesthesia during Caesarean Section: A Randomized Controlled Trial - Aysenur Dostbil; Canan Atalay; Ilker Ince; Mehmet Aksoy; Ozgur Ozmen; Kamber Kasali; Omer Erkan Yapca; Tugberk Kucun; Ayse Nur Aksoy; Gamze Nur Cimilli Senocak (IMR Press, 2023)
Background: The objective of this study was to conduct a randomized controlled trial in order to examine the hemodynamic impacts of two different doses of intrathecal isobaric bupivacaine (5 mg and 7 mg) when combined with 15 µg fentanyl in the context of patients undergoing caesarean section under combined spinal epidural anesthesia. Methods: Eighty patients with American Society of Anesthesiologists physical status I and II, aged between 16-50 years, who would undergo elective caesarean section under combined spinal epidural anaesthesia were randomly allocated to Group A and Group B (n = 40, for each group). Group A patients received a solution containing 5 mg isobaric bupivacaine + 15 µg fentanyl (1.3 mL), while Group B patients received a solution containing 7 mg isobaric bupivacaine + 15 µg fentanyl (1.7 mL) intrathecally. Incidences of hypotension, intraoperative systolic blood pressure, diastolic blood pressure, heart rate, motor block resolving time, and analgesia duration were recorded. Results: Group A had a substantially lower incidence of hypotension than Group B (p = 0.022). Patients in Group B had significantly lower systolic blood pressure values at the 6th, 8th, 10th, 12th, 14th, 15th, and 30th minutes of the surgery compared to Group A (p = 0.012, p = 0.014, p = 0.005, p = 0.016, p < 0,001, p = 0.002, and p = 0.011; respectively). Both groups had similar diastolic blood pressure and heart rate values during surgery (p > 0.05). The motor block resolving time and analgesia duration were longer in Group B compared to Group A (p < 0.001 for both). Two (5%) patients in Group A and ten (25%) patients in Group B experienced postoperative itching (p = 0.012). Conclusions: We concluded that combining 5 mg isobaric bupivacaine with 15 mcg of fentanyl administered intrathecally provides adequate anaesthesia while maintaining better hemodynamic stability in patients undergoing caesarean section. Clinical Trial Registration: The study has been registered with registration number NCT05136040 on https://classic.clinicaltrials.gov/ct2/results?cond=&term=+NCT05136040&cntry=&state=&city=&dist=.